Prolonged maternal exposure to glucocorticoids alters selenoprotein expression in the developing brain - Toh, Pamela; Seale, Lucia A.; Berry, Marla J.; Torres, Daniel J. (Frontiers in Molecular Neuroscience, 2023)
Aberrant activation of the stress-response system in early life can alter neurodevelopment and cause long-term neurological changes. Activation of the hypothalamic–pituitary–adrenal axis releases glucocorticoids into the bloodstream, to help the organism adapt to the stressful stimulus. Elevated glucocorticoid levels can promote the accumulation of reactive oxygen species, and the brain is highly susceptible to oxidative stress. The essential trace element selenium is obtained through diet, is used to synthesize antioxidant selenoproteins, and can mitigate glucocorticoid-mediated oxidative damage. Glucocorticoids can impair antioxidant enzymes in the brain, and could potentially influence selenoprotein expression. We hypothesized that exposure to high levels of glucocorticoids would disrupt selenoprotein expression in the developing brain. C57 wild-type dams of recently birthed litters were fed either a moderate (0.25 ppm) or high (1 ppm) selenium diet and administered corticosterone (75 μg/ml) via drinking water during postnatal days 1 to 15, after which the brains of the offspring were collected for western blot analysis. Glutathione peroxidase 1 and 4 levels were increased by maternal corticosterone exposure within the prefrontal cortex, hippocampus, and hypothalamus of offspring. Additionally, levels of the glucocorticoid receptor were decreased in the hippocampus and selenoprotein W was elevated in the hypothalamus by corticosterone. Maternal consumption of a high selenium diet independently decreased glucocorticoid receptor levels in the hippocampus of offspring of both sexes, as well as in the prefrontal cortex of female offspring. This study demonstrates that early life exposure to excess glucocorticoid levels can alter selenoprotein levels in the developing brain.